Understanding the basis of differential auxin response in selected plant species - XIE, Chenkai (2025)
Auxin plays a pivotal role in regulating root development and the molecular andcellular basis of this process has been well described in model plant Arabidopsis thaliana. However, our understanding of these mechanisms in other plant species remains limited. To explore the conservation of auxin responses across species, we treated three plant species - Brachypodium, rice, and foxtail millet - with varying concentrations of auxin and analysed their primary root growth response. Additionally, we conducted RNA sequencing to identify differentially expressed genes (DEGs) under one optimised auxin concentration. Comparative DEG analysis and promoter analysis revealed the conservation of the classic auxin signaling pathway while highlighting potential species-specific variations in auxin sensitivity and response.